The Clinical Significance Of Npm1, Flt3 And Cebpa Gene Mutations In Adult Patients With Acute Myeloid Leukaemia - Ul Haq, Izaz (2020)
Acute myeloid leukaemia (AML) is a biologically complex and clinically heterogeneous haematological cancer, and its incidence increases in the elderly. Age, cytogenetics and genetic mutations remain important prognostic factors for treatment outcome. The main aim of the study was to determine the prevalence and clinical significance of NPM1, FLT3 and CEBPA mutations of AML in the Peninsula Malaysia. Three common and important gene mutations in AML FLT3 (exon 14-15, exon 20), NPM1 (exon 12), and CEBPA (exon 1) were determined by polymerase chain reaction and conformation-sensitive gel electrophoresis (CSGE) in 47 newly diagnosed adult patients with AML. Fisher-Exact Test was used to analyse the significant difference of AML with FLT3-ITD, NPM1, and CEBPA mutants in association with the clinical parameters.